Lateral Versus Anterior Approach Laparoscopic Splenectomy: A Randomized-controlled Study. Issue 6 (December 2016) - Fathi, Adel; Eldamshety, Osama; Bahy, Osama; Denewer, Adel; Fady, Tamer; Shehatto, Fayez; Khater, Ashraf; Elnahas, Waleed; Roshdy, Sameh; Farouk, Omar; Senbel, Ahmed; Hamed, Emad-Eldeen; et al.
Abstract : Purpose of the Study: The study compares prospectively the hospital stay and postoperative complications of anterior (ALS) versus lateral (LLS) approach for laparoscopic splenectomy. Materials and Methods: Between September 2011 and April 2015, 94 patients with splenomegaly were referred to the surgical unit in the Oncology Center of Mansoura University, Egypt. Only 80 patients with splenomegaly <30 cm underwent an open-label randomized allocation into 2 equal parallel groups. Indications were hematological in 52 patients (65%) and malignant splenic conditions in 28 patients (35%). Two patients younger than 18 years, 4 patients with splenomegaly >30 cm, and 8 patients with associated surgical comorbidities were excluded. Three days' hospital stay reduction with LLS was suggested with a power of 80% and P -value of 0.05. Results: The mean hospital stay was significantly shorter ( P =0.001) after LLS. Laparoscopic splenectomy was completed in 68 patients (85%). Twelve patients (15%) required open splenectomy with no difference between groups. The operation time was significantly shorter in LLS ( P =0.013). Blood loss ( P =0.057) and blood transfusion ( P =0.376) showed no difference between the two groups. The times until resumption of oral intake ( P =0.019) and drain removal ( P =0.011) were statistically shorter in LLS. Conclusions: LLS is more safe and feasible with shorter hospital stay compared with ALS.